RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF ADOLESCENTS ON THE USE OF CONTACT LENSES AND THE RISK OF DRY EYES IN FEMALE STUDENTS OF SMAN 1 RAWAMERTA IN 2023 - Encep Ahmad Abdurahman; Lisna Agustina; Lina Indrawati (Rena Cipta Mandiri, 2024)
Contact lenses are visual aids that are placed on the cornea of ​​the eye, easy to use, comfortable for activities, provide a wider field of view, and are aesthetically better. Contact lenses were originally discovered as technology developed as a substitute for glasses in people with refractive disorders. Most refractive errors in the eye can be treated with refractive correction, refractive errors can be done by using vision aids such as glasses. However, the existence of contact lenses to help vision and LASIK surgery is starting to become an alternative for eyeglass users. The design in this study uses a cross sectional approach. Cross Sectional is an analytical research design that aims to determine the relationship between variables where the independent variables and dependent variables are identified at one time. the results of statistical analysis using the Chi Square test, it was obtained a p value of 0.000, it can be concluded that the p value is (0.000) < (0.05) so that it can be stated that H0 is rejected, namely there is a relationship between the level of knowledge of adolescents on the use of contact lenses and the risk of dry eyes in high school students 1 Rawamerta in 2023” Lensa kontak adalah alat bantu penglihatan yang ditempatkan di kornea mata, mudah digunakan, nyaman untuk beraktivitas, memberikan lapang pandang lebih luas, dan lebih baik secara estetik. Lensa kontak pada awalnya ditemukan seiring berkembangnya teknologi sebagai pengganti kacamata pada penderita gangguan refraksi. Kebanyakan kelainan refraksi pada mata dapat diatasi dengan koreksi refraksi, kelainan refraksi dapat dilakukan dengan penggunaan alat bantu penglihatan seperti kacamata. Namun keberadaan lensa kontak untuk membantu penglihatan serta operasi lasik mulai menjadi alternatif bagi pengguna kaca mata. Desain dalam penelitian ini menggunakan pendekanan Cross Sectional. Cross Sectional adalah sebuah desain penelitian analitik yang bertujuan untuk mengetahui hubungan antar variabel yang dimana variabel independen dan variabel dependen di identifikasi dalam satu waktu. hasil analisa statistik dengan menggunakan uji Chi Square diperoleh p value 0,000 dapat disimpulkan p value (0,000) < (0,05) sehingga dapat dinyatakan bahwa H0 ditolak yaitu ada “hubungan tingkat pengetahuan remaja pada penggunaan lensa kontak dengan resiko dry eyes pada siswi SMAN 1 Rawamerta tahun 2023”.